Productivity Enhancement in Teak Plantations - Prakash, Ram; Shukla, P. K. (Indian Forester, 2010)
India has the largest share (44%) of teak plantations but the average recorded productivity of India’s forest is 0.5 cum/ha/yr as compared to the world average of 2.5 cum/ha/yr while the potential productivity of Indian Forest is estimated as 11.5 cum/ha/yr. Significant developments have taken place in standardizing plantation techniques, perfecting harvesting and post harvest utilization methods and tree improvement. Plantation technology, silvicultural practices, disease and pest management, tree improvement, genetic improvements and protection etc. plays an important role in enhancing the forest productivity. Silvicultural practices like site selection, spacing, thinning methods, rotation age and harvesting have been refined, yet the productivity of plantations is low. Recent studies conducted on teak growing with irrigation, fertilizer application and management revealed the possibility of reducing the rotation to 25-30 years period with increase in productivity as against the dry teak plantations.